Osteogenetic mechanism and clinical surgical selection of maxillary sinus floor elevation - XU Shuyu; FAN Zhen; WANG Zuolin (Kouqiang hemian waike zazhi)
The maxillary sinus floor elevation surgery through the crest of the alveolar ridge is a commonly used method to solve the problem of insufficient residual bone height (RBH) required for implant restoration in the posterior maxillary region. There are currently many controversies relating to this operation, including the mechanism of osteogenesis in the maxillary sinus, the selection of surgical methods for maxillary sinus floor elevation, the timing of simultaneous implantation, the impact of age or gender, and the need for bone substitutes. Based on the research of our group on the mechanism of maxillary sinus osteogenesis, combined with the treatment effect of maxillary sinus floor elevation surgery in the Department of Oral Implantology in our hospital for over 10 years. This article summarizes the clinical operation rules and internal correlations in order to achieve the translational medicine model that combines theoretical research with clinical practice and ultimately guides clinical practice. A summary of the methods and techniques for clinical operations has been outlined in order to achieve a combination of theoretical research and practical clinical guidance, proposing a more optimized and simplified solution and the concept for maxillary sinus floor elevation surgery called transalveolar maxillary sinus floor elevation (TSFE), which involves the use of concentrated growth factors (CGF) and simultaneous implantation of dental implants.